Risks and benefits of prophylactic inferior vena cava filters in patients undergoing bariatric surgery. Issue 4 (8th February 2013) - Birkmeyer, Nancy J.; Finks, Jonathan F.; English, Wayne J.; Carlin, Arthur M.; Hawasli, Abdelkader A.; Genaw, Jeffrey A.; Wood, Michael H.; Share, David A.; Birkmeyer, John D.
<x xml:space="preserve">Abstract</x> BACKGROUND The United States Food and Drug Administration recently issued a warning about adverse events in patients receiving inferior vena cava (IVC) filters. OBJECTIVE To assess relationships between IVC filter insertion and complications while controlling for differences in baseline patient characteristics and medical venous thromboembolism prophylaxis. DESIGN Propensity‐matched cohort study. SETTING The prospective, statewide, clinical registry of the Michigan Bariatric Surgery Collaborative. PATIENTS Bariatric surgery patients (n=35, 477) from 32 hospitals during the years 2006 through 2012. INTERVENTION Prophylactic IVC filter insertion. MEASUREMENTS Outcomes included the occurrence of complications (pulmonary embolism, deep vein thrombosis, and overall combined rates of complications by severity) within 30 days of bariatric surgery. RESULTS There were no significant differences in baseline characteristics among the 1, 077 patients with IVC filters and in 1, 077 matched control patients. Patients receiving IVC filters had higher rates of pulmonary embolism (0.84% vs 0.46%; odds ratio [OR], 2.0; 95% confidence interval [CI], 0.6‐6.5; P=0.232), deep vein thrombosis (1.2% vs 0.37%; OR, 3.3; 95% CI, 1.1‐10.1; P=0.039), venous thromboembolism (1.9% vs 0.74%; OR, 2.7; 95% CI, 1.1‐6.3, P=0.027), serious complications (5.8% vs 3.8%; OR, 1.6; 95% CI, 1.0‐2.4; P=0.031), permanently disabling complications (1.2% vs 0.37%; OR, 4.3; 95% CI, 1.2‐15.6; P=0.028), and death (0.7% vs 0.09%; OR, 7.0; 95% CI, 0.9‐57.3; P=0.068). Of the 7 deaths among patients with IVC filters, 4 were attributable to pulmonary embolism and 2 to IVC thrombosis/occlusion. CONCLUSIONS We have identified no benefits and significant risks to the use of prophylactic IVC filters among bariatric surgery patients and believe that their use should be discouraged. Journal of Hospital Medicine 2013;8:173–177. © 2013 Society of Hospital Medicine